Original papersRole of E-selectin and platelet endothelial cell adhesion molecule 1 in gastritis in food allergy patients - Graczyk, Małgorzata; Przybyszewski, Michał; Kuźmiński, Andrzej; Tlappa, Jacek; Mućka, Jacek; Napiórkowska, Katarzyna; Szynkiewicz, Ewa; Żbikowska-Gotz, Magdalena; Bartuzi, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction : The prevalence of food allergies and other allergic reactions is increasing worldwide, particularly in highly-urbanized populations. Cell adhesion molecules are expressed in response to various pro-inflammatory cytokines. The expression of intercellular adhesion molecule 1 – ICAM-1 (CD54), ICAM-1 (CD106), P-selectin (CD62P), and E-selectin (CD62E) on vascular endothelial cells is induced by such pro-inflammatory cytokines as tumor necrosis factor α (TNF-α) and interleukin-1 (IL-1). Aim: To analyze concentrations of E-selectin and platelet endothelial cell adhesion molecule-1 (PECAM-1) in patients with an allergic type of food sensitivity co-existing with gastritis and to compare them to the values determined in individuals with dyspeptic symptoms not associated with allergic disorders. Material and methods : The study included 80 patients, among them 50 individuals with food sensitivity confirmed based on compulsory standards, and 30 subjects with dyspeptic symptoms not accompanied by allergic conditions. Venous blood samples were taken from each patient and concentrations of E-selectin and PECAM-1 were determined by means of ELISA. Results: Mean concentrations of sE-selectin and sPECAM-1 in patients with food allergy amounted to 54.0 ±21.6 ng/ml and 132.8 ±31.4 ng/ml, respectively. In individuals without food allergy, mean concentrations of sE-selectin and sPECAM-1 were 57.7 ±17.9 ng/ml and 139.6 ±31.1 ng/ml, respectively. Patients with food allergy and individuals with dyspeptic symptoms not associated with food allergy did not differ significantly in terms of sE-selectin concentrations (Mann-Whitney U-test, p = 0.453028). Similarly, no significant intergroup differences were observed with regard to sPECAM-1 concentrations (Mann-Whitney U-test, p = 0.231054). Conclusions : Adhesion molecules play an important role in the development of inflammation. This study did not find significant differences in the concentrations of such molecules as sE-selectin and sPECAM-1 between patients with food allergy and gastritis, and subjects in whom gastritis was not accompanied by atopic disorders. A positive correlation between the concentrations of sPECAM-1 and E-selectin was observed in food allergy patients. Consequently, it can be concluded that these molecules participate in the pathogenesis of the inflammatory process independently of the etiopathogenesis of gastritis.